2011
DOI: 10.2478/v10102-011-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the vascular endothelium in experimental situations

Abstract: One of the factors proposed as mediators of vascular dysfunction observed in diabetes is the increased generation of reactive oxygen species (ROS). This provides support for the use of antioxidants as early and appropriate pharmacological intervention in the development of late diabetic complications. In streptozotocin (STZ)-induced diabetes in rats we observed endothelial dysfuction manifested by reduced endothelium-dependent response to acetylcholine of the superior mesenteric artery (SMA) and aorta, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Oxidative stress is involved in atherogenesis, which is initiated by endothelial injury in cases with cardiovascular risk factors, including diabetes mellitus, hypertension, cigarette smoking, dyslipidemia, obesity, and metabolic syndrome (Husain et al 2015;Salmanoglu et al 2016). Participation of oxidative stress in induction of endothelial dysfunction was confirmed by the beneficial action of antioxidants which were able to suppress the detrimental effect of reactive oxygen species (Sotníková et al 2008(Sotníková et al , 2011. Results of Requintina and Oxengruk (2003) indicated that the effect of LPS on lipid peroxidation is dose-, time-, and species-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is involved in atherogenesis, which is initiated by endothelial injury in cases with cardiovascular risk factors, including diabetes mellitus, hypertension, cigarette smoking, dyslipidemia, obesity, and metabolic syndrome (Husain et al 2015;Salmanoglu et al 2016). Participation of oxidative stress in induction of endothelial dysfunction was confirmed by the beneficial action of antioxidants which were able to suppress the detrimental effect of reactive oxygen species (Sotníková et al 2008(Sotníková et al , 2011. Results of Requintina and Oxengruk (2003) indicated that the effect of LPS on lipid peroxidation is dose-, time-, and species-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…ESM-1 level was significantly elevated in the model group, which is also regulated by proinflammatory cytokines. The serum ESM-1 level was normal in healthy subjects, whereas the serum ESM-1 level was significantly increased in patients with acute and severe sepsis [30]. Resuscitation using 6 % HES 130/0.4 ?0.9 % saline played a role in suppressing the inflammatory response and also led to a restored tendency of ESM-1 level compared to the model group.…”
Section: Discussionmentioning
confidence: 99%
“…Further significant property of SMe1EC2 was its ability to protect endothelium under conditions of experimental diabetes of rats. It significantly decreased endothelaemia of diabetic rats and improved endothelium-dependent relaxation of arteries, slightly decreased ROS-production and increased bioavailability of nitric oxide in the aorta (Sotníková et al, 2011 ). Overall, the compound attenuated endothelial injury in diabetic animals.…”
Section: Antioxidant Properties In An Example Mtdlmentioning
confidence: 99%